Phenotypic heterogeneity in the gray platelet syndrome extends to the expression of TREM family member, TLT-1 - Nurden, Alan T.; Nurden, Paquita; Bermejo, Emilsé; Combrié, Robert; McVicar, Daniel W.; Washington, A.Valance (Thrombosis and Haemostasis, 2008)
The Gray platelet syndrome (GPS) is a rare inherited disorder linked to undefined molecular abnormalities that prevent the formation and maturation of α-granules. Here, we report studies on two patients from unrelated families that confirm phenotypic heterogeneity in the disease. First we used immunoelectron microscopy (I-EM) to confirm that TREM-like transcript-1 (TLT-1) is mostly localized to α-granule membranes of normal platelets. Then we performed Western blotting (WB) and flow cytometry with permeabilized platelets to show that TLT - 1 is selectively reduced in the platelets of patient 1, previously noted to be deficient in glycoprotein (GP)VI (Nurden et al., Blood 2004; 104: 107–114).Yet both TLT - 1 and GPVI were normally expressed in platelets of patient 2. Usual levels of JAM-C and claudin-5, also members of the immunoglobulin receptor family, were detected in platelets of both patients. In contrast, P-selectin was markedly decreased for patient 1 but not patient 2.Two metalloproteases, MMP-2 and MMP-9 were normally present. As predicted, platelets of patient 1 showed little labelling for TLT - 1 in I-EM, whereas residual Fg was seen in small vesicular structures and P-selectin lining vacuoles or channels of what may be elements of the surface-connected canalicular system. Our results identify TLT - 1 as a glycoprotein potentially targeted in platelets of GPS patients, while decreases in at least three membrane glycoproteins suggest that an unidentified proteolytic activity may contribute to the phenotype in some patients with this rare disease.
Keywords: Gray platelet syndrome; inherited / acquired platelet disorders; protein trafficking; secretion / exocytosis